Ebola and Beyond-Developing an Infectious Diseases Treatment Infrastructure in the United States. (4th October 2017) - Vanairsdale, Sharon; Mehta, Aneesh K; Kraft, Colleen
Abstract: Background: From 2014 to 2016, West Africa experienced the largest outbreak of Ebola in history. While a few hospitals successfully managed several patients with Ebola Virus Disease, gaps within the U.S. healthcare system became evident after two nurses were infected with Ebola while providing patient care to a patient with Ebola. In 2015, the U.S. Department of Health and Human Services (HHS) initiated programs to address Ebola clinical care preparedness and response. Methods: In response to the 2014 Ebola outbreak in West Africa, the U.S. Department of HHS sought to increase the competency of healthcare and public health workers and capabilities of healthcare facilities in the U.S. to deliver safe and effective care to patients with Ebola and other special pathogens. The National Ebola Training and Education Center (NETEC), a collaboration between three facilities who successfully treated patients with Ebola, was established. The NETEC serves as an infrastructure to disseminate best practices, standardize patient care, expedite experimental therapeutics and improve the safety for patients and healthcare professionals. Results: The Assistant Secretary for Preparedness and Response and the Centers for Control and Prevention have designated ten Regional Treatment Centers. The NETEC has created assessment metrics, training materials, drills, etc to support these facilities. To date, over 2000 healthcare professionals have benefited from NETEC. Conclusion: Many of the gaps in outbreak preparedness within the U.S. healthcare systems are being addressed by NETEC and the ten regional Ebola treatment centers. This system has growing capacity to effectively identify, isolate, transport and treat patients with serious communicable and novel infections with appropriate clinical containment measures. The NETEC continues to expand the capacities of the U.S. healthcare system to face these challenges in order to care for these patients while protecting the safety of healthcare workers, healthcare systems and the community. It is critical to maintain continued preparedness to manage the future threats. Disclosures: All authors: No reported disclosures.